Efek Prolonged Sitting Saat Work from Home (WFH) Pada Para Pekerja Selama Pandemik Covid-19 - Cicilia Hayuningrum (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Covid-19 pandemic situation has led to working pattern changes to working from home. The implementation of WFH led to a significant increase in the duration of sitting among workers which then induce physical inactivity. Physical inactivity. characterized by prolonged sitting generated several impacts on various aspect of body function and movement, including the musculoskeletal system, metabolism, immunity, inflammation and oxidative stress. This article aims to further analyze the effects of prolonged sitting on human’s body system organs and function. Previous study proved that prolonged sitting during WFH led to increase pain in the neck, shoulders, upper back and lower back regions. Moreover, prolonged sitting also induced insulin resistance conditions which disrupt glucose metabolism. Furthermore, prolonged sitting was able to enhance various biomarker of inflammation, as long as oxidative stress. meanwhile, active breaks with light to moderate intensity activities, during prolonged sitting proved to significantly increase the body’s immune markers and anti-oxidant defense. Thus, the implementation of WFH should be interspersed with low to moderate intensity of physical activity